2011
DOI: 10.1016/j.cellsig.2010.08.003
|View full text |Cite
|
Sign up to set email alerts
|

The diverse functions of GAPDH: Views from different subcellular compartments

Abstract: Multiple roles for glyceraldehyde-3-phosphate dehydrogenase (GAPDH) have been recently appreciated. In addition to the cytoplasm where majority of GAPDH is located under the basal condition, GAPDH is also found in the particulate fractions, such as the nucleus, the mitochondria, and the small vesicular fractions. When cells are exposed to various stressors, dynamic subcellular re-distribution of GAPDH occurs. Here we review these multifunctional properties of GAPDH, especially linking them to its oligomerizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
489
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 554 publications
(501 citation statements)
references
References 86 publications
8
489
0
4
Order By: Relevance
“…[38][39][40][41][42]70,[85][86][87] In the following we discuss three topics: (a) the use of sucrose gradient fractionation in MS-based proteomics to obtain data about subcellular spatial distribution of proteins, (b) how the observed distributions might be related to MCF7 cells as cancer cells, and (c) the implications of our results for how such spatial distributions may relate to overall control of cellular function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[38][39][40][41][42]70,[85][86][87] In the following we discuss three topics: (a) the use of sucrose gradient fractionation in MS-based proteomics to obtain data about subcellular spatial distribution of proteins, (b) how the observed distributions might be related to MCF7 cells as cancer cells, and (c) the implications of our results for how such spatial distributions may relate to overall control of cellular function.…”
Section: Discussionmentioning
confidence: 99%
“…103,104 Furthermore, the spatial/functional dispersion of proteins can be connected to a plethora of different post-translational modifications, as exemplified by the wide-ranging, different functionalities of GAPDH. 85,86 Complementation of full-proteome scans using bottom-up proteomics with top-down proteomics methods that could rapidly and routinely fully characterize the transcriptional and post-translational features of a few tens of selected proteins seems to be a remaining task for proteomics. It would be desirable that conventional biological experiments, are routinely accompanied by verification by MSbased proteomics of the exact structures for the crucial proteins.…”
Section: The Influence Of Subcellular Protein Distributions On Cellulmentioning
confidence: 99%
“…Au tophagy is in di rectly mod u lated by meta bolic en zymes. Glyc er alde hyde 3 phos phate de hy dro ge nase (GAPDH) is in volved in mul ti ple cel lu lar processes based mainly on its sub cel lu lar lo cal iza tion [144]. Dur ing glu cose de pri va tion, GAPDH is phos pho ry lated by AMPK and is translo cated to the cell nu cleus where it in ter acts with NAD de pen dent deacety lase sir tuin 1 (Sirt1).…”
Section: Metabolic Regulation Of Cancer Cell Deathmentioning
confidence: 99%
“…However, a pea (Pisum sativum) chloroplast GAPDH isoform has been shown to have uracil DNA glycosylase activity (Wang et al, 1999), and in mammals, GAPDH was shown to fulfill additional nonmetabolic functions, including posttranscriptional regulation, maintenance of DNA integrity, and apoptosis (Sirover, 2011;Tristan et al, 2011). In rat cells, stress conditions may cause nitrosylation of GAPDH catalytic Cys and interaction with Seven in absentia homolog1 (Siah1; an E3 ubiquitin ligase), whose nuclear localization signal drives the GAPDH-Siah1 complex into the nucleus, where the ubiquitinating activity of Siah1 promotes apoptosis (Hara et al, 2005).…”
mentioning
confidence: 99%